Efek Analgetik Ekstrak Etanol Daun Tapak Liman (Elephantopus scaber L.) Pada Mencit Putih Jantan - Surya Dharma; Adirman Adirman; Elisma Elisma (STIFARM Padang, 2013)
Study about the analgesic effect of aethanolic extract of tapak liman leaf (Elephantopus scaber L) of white mice mice induced acetat acid 1% has been done. Extract was administered orally of variation dose 100, 300 and 900 mg/bw once daily until 7, 14 and 21 day. Results showed that giving of aethanolic extract of tapak liman leaf could decreased amount of stretching significantly.